A comprehensive discussion of HMBC pulse sequences. III. Solving the problem of missing and weakly observed long‐range correlations. (20th March 2015) - Furrer, Julien
ABSTRACT: The intensity of long‐range correlations observed with the classical HMBC pulse sequence using static optimization of the long‐range coupling delay is directly related to the size of the coupling constant and is often set as a compromise. As such, some long‐range correlations might appear with a reduced intensity or might even be completely absent from the spectra. After a short introduction, this third manuscript will give a detailed review of some selected HMBC variants dedicated to improve the detection of long‐range correlations, such as the ACCORD‐HMBC, CIGAR‐HMBC, and Broadband HMBC experiments. Practical details about the accordion optimization, which affords a substantial improvement in both the number and intensity of the long‐range correlations observed, but introduces a modulation in F 1, will be discussed. The incorporation of the so‐called constant time variable delay in the CIGAR‐HMBC experiment, which can trigger or even completely suppress 1 H– 1 H coupling modulation inherent to the utilization of the accordion principle, will be also discussed. The broadband HMBC scheme, which consists of recording a series of HMBC spectra with different delays set as a function of the long‐range heteronuclear coupling constant ranges and transverse relaxation times T 2, is also examined. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part A 43A: 177–206, 2015.